Identifying the superior measure of rapid fibrosis for predicting premature cirrhosis after liver transplantation for hepatitis C. Issue 6 (13th September 2013) - Howell, J.; Sawhney, R.; Angus, P.; Fink, M.; Jones, R.; Wang, B.Z.; Visvanathan, K.; Crowley, P.; Gow, P.
Abstract Background Hepatitis C virus (HCV) recurrence post liver transplant is universal, with a subgroup of patients developing rapid hepatic fibrosis. Various clinical definitions of rapid fibrosis (RF) have been used to identify risks for rapid progression, but their comparability and efficacy at predicting adverse outcomes has not been determined. Methods Retrospective data analysis was conducted on 100 adult patients with HCV who underwent liver transplantation at a single center. We measured year 1 fibrosis progression (RF defined as METAVIR F score ≥1 at 1‐year liver biopsy), time to METAVIR F2‐stage fibrosis, and fibrosis rate (calculated using liver biopsies graded by METAVIR scoring F0–4; fibrosis rate = fibrosis stage/year post transplant). RF was defined as ≥0.5 units/year. Results Multivariate analysis revealed that donor age and peak HCV viral load were significant risks for RF, when fibrosis rate was used to define RF. Advanced donor age was a risk for rapid progression to F2‐stage fibrosis, whereas genotype 2 or 3 HCV infection was protective. Fibrosis rate had the strongest correlation with time to cirrhosis development (P < 0.0001, r = −0.76) and was the most accurate predictor of rapid graft cirrhosis (P < 0.0001, area under the curve 0.979, sensitivity 100%, specificity 94%). Conclusion Different measures of RF progression identify different risks for RF and are not directly comparable. Fibrosis rate was the most accurate predictor of rapid graft cirrhosis.